Kubord 2: Word relations Svenska Dagbladet 2010 - Språkbanken Text (University of Gothenburg, 2024)
Part of the collection Kubord 2

Del av samlingen Kubord 2
Kubord 2: Ordrelationer Svenska Dagbladet 2010
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik